Australia : Selected Issues. (IMF Staff Country Reports; Country Report, 2009)
This paper analyzes likely effectiveness of the fiscal policy in supporting aggregate demand in Australia. The simulation analysis illustrates that the type of fiscal measure and the underlying behavioral responses have an important impact on the magnitude of fiscal multipliers. The Global Integrated Monetary and Fiscal Model simulations also suggest that the cumulative impact after five years could be close to 10 percentage points of GDP for the announced stimulus measures that cumulate to almost 8 percentage points of GDP.